2002
DOI: 10.1021/ja016508z
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Substituent Effects in Offset π−π Stacked Interactions in Water

Abstract: We have measured the rotational barriers of meta- and para-substituted N-benzyl-2-(2-fluorophenyl)pyridinium bromides in aqueous solution by dynamic NMR as a model system for offset-stacking interactions in proteins. Because the benzyl ring can stack with the 2-fluorophenyl ring in the offset conformation in the ground state, but not the transition state, the rotational barrier reflects the magnitude of the stacking interaction. Only a small (0.1 kcal/mol) change in rotational barrier was found for para substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
161
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(181 citation statements)
references
References 13 publications
14
161
0
3
Order By: Relevance
“…37 The interactions of S···C2 (3.576 Å), − (−0.88946). Nowadays it seems quite well accepted that hydrogen bonding influences the structures of ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…37 The interactions of S···C2 (3.576 Å), − (−0.88946). Nowadays it seems quite well accepted that hydrogen bonding influences the structures of ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in nonpolar solvents using aromatic compounds containing various electron-donating and -withdrawing substituents have demonstrated significant electrostatic effects in stacking energetics and geometries. [15][16][17] Although in aqueous systems the electrostatic dipole effects are greatly diminished, localized electrostatic effects are still believed to play a role in governing neighboring base-pair geometries in DNA. [6,12] Studies with smallmolecule model systems in water have suggested that electrostatic effects are relatively weak, and that dispersive effects are a major factor governing stacking stability.…”
mentioning
confidence: 99%
“…2). The electrostatic potential surfaces of these molecules [39][40][41][42][43] generated by means of computer calculations 43) are shown in the lower part of Fig. 2.…”
Section: Resultsmentioning
confidence: 99%